The Economic Impacts of Climate Change: Evidence from Agricultural Profits and Random Fluctuations in Weather - Michael Greenstone; Olivier Deschenes (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper measures the economic impact of climate change on US agricultural land by estimating the effect of the presumably random year-to-year variation in temperature and precipitation on agricultural profits. Using long-run climate change predictions from the Hadley 2 Model, the preferred estimates indicate that climate change will lead to a 1.1 billion (2002) or 3.4% increase in annual profits. The 95% confidence interval ranges from -1.8 billion to 4.0 billion and the impact is robust to a wide variety of specification checks, so large negative or positive effects are unlikely. There is considerable heterogeneity in the effect across the country with Californias predicted impact equal to -2.4 billion (or nearly 50% of state agricultural profits). Further, the analysis indicates that the predicted increases in temperature and precipitation will have virtually no effect on yields among the most important crops. These crop yield findings suggest that the small effect on profits is not due to short-run price increases. The paper also implements the hedonic approach that is predominant in the previous literature. We conclude that this approach may be unreliable, because it produces estimates of the effect of climate change that are very sensitive to seemingly minor decisions about the appropriate control variables, sample and weighting. Overall, the findings contradict the popular view that climate change will have substantial negative welfare consequences for the US agricultural sector.
Keywords: Q50; Q12; Q54; Q51; 330; Cost of climate change; Hedonics; Agricultural profits; Agricultural production; Crop yields; Klimaveränderung; Landwirtschaft; Agrareinkommen; USA; Makroökonomischer Einfluss